REVEALING SPATIAL REPRESENTATION THROUGH WALKING ALONG THE CULTURAL CORRIDOR IN YOGYAKARTA - Wardhani, Mustika Kusumaning; Suprapti, Atik; Harani, Arnis Rochma; Kurniati, Rina (International Journal on Livable Space, 2026)
Background: Spatial representation typically focuses on physical dimensions overlooking the relationships between subjects and objects encountered during urban navigation. By reframing cinematic interpretation from a visual arts perspective to one of urban legibility, however, we can more effectively examine spatial representation within actual urban contexts. Aims: This study aims to examine how walking experiences shape the subject-object relations in cultural corridors. Furthermore, the study aims to translate these narratives through montage analysis to reveal aspects of public space that influence cinematic experiences. Methodology and Results: This study uses a qualitative, single-case study approach to investigate the elements of urban space that attract domestic tourists. Forty-one tourists shared their interests, and their spatial narratives presented nine distinct episodes. The study reveals that static objects enhance the visual landscape, while temporary objects facilitate movement and create intermezzo moments. Conclusion, significance, and impact study: These findings demonstrate that spatial narratives offer valuable insights into how sequences of events in a particular urban corridor can shape cinematic experiences. The study's impact lies in showing that pedestrian-based spatial narratives can be a practical design tool for visual route planning, preserving cultural identity, and enhancing walkability in historic urban corridors.